PENGEMBANGAN UMKM DAN EKONOMI KREATIF MELALUI PEMBUATAN KERIPIK USUS - Elvania, Nindy Callista; Sofyan, Ade; Maulana, Ilham Ridho; Dwi Putra, Hafit Cahyono (Jurnal Abdi Masyarakat, 2023)
Sikeyyan is a Small and Medium Sized Enterprises in Beged Village, Gayam District, Bojonegoro Regency. These Small and Medium Sized Enterprises do not have social media accounts to sell online. This is what makes intestinal chips products not very well known among the public. Product marketing is also limited, only in the area of origin, namely Beged Village, Gayam District, Bojonegoro Regency. From the problem, we provide assistance for Small and Medium Sized Enterprises starting from the aspect of product quality in the form of procuring oil slicing machines, creating social media accounts such as Instagram, Facebook, Shopee as well as product promotion and marketing through online media. So that it can improve product quality and be able to operate oil slicing machines independently, social media, product marketing through online media to increase the turnover of Small and Medium Sized Enterprises products and improve the welfare of rural communities. The resulting output is product quality, product packaging standards for Small and Medium Sized Enterprises, promotional media and online marketing through social media.